SMART PAPER BERBASIS QR-CODE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SEKOLAH DASAR - Putra, Galih Mahardika Christian; Pramesti, Yulistiya Putri (Universitas Muria Kudus, 2024)
The aim of this research is to design, test the feasibility and effectiveness of QR-Codebased Smart Paper as a learning medium in improving the critical thinking skills ofelementary school students through social studies learning content.The research method used is Research and Development (RD) with the Borg Galldevelopment model. Data collection techniques used include observation, interviews,questionnaires, tests and documentation. The initial data analysis technique used thenormality test and homogeneity test. Next, the final data analysis technique used theaverage difference test and the N-Gain test.The research results show that QR-Code based Smart Paper has been successfullydeveloped. This is proven by the validation results of material experts 91.67% and mediaexperts 96.67% with very appropriate criteria. Furthermore, the calculated results of theN-Gain test on the learning outcomes aspect obtained a score of 0.57 with medium criteria and the results of the average difference test obtained a sig (2-tailed) value 0.05, so Ha was accepted. So it can be concluded that QR-Code based Smart Paper is a suitable and effective learning medium for improving students' critical thinking skills.